Osteopontin at the Crossroads of Inflammation and Tumor Progression. (9th July 2017) - Castello, Luigi Mario; Raineri, Davide; Salmi, Livia; Clemente, Nausicaa; Vaschetto, Rosanna; Quaglia, Marco; Garzaro, Massimiliano; Gentilli, Sergio; Navalesi, Paolo; Cantaluppi, Vincenzo; Dianzani, Umberto; Aspesi, Anna; et al.
Abstract : Complex interactions between tumor and host cells regulate systemic tumor dissemination, a process that begins early at the primary tumor site and goes on until tumor cells detach themselves from the tumor mass and start migrating into the blood or lymphatic vessels. Metastatic cells colonize the target organs and are capable of surviving and growing at distant sites. In this context, osteopontin (OPN) appears to be a key determinant of the crosstalk between cancer cells and the host microenvironment, which in turn modulates immune evasion. OPN is overexpressed in several human carcinomas and has been implicated in inflammation, tumor progression, and metastasis. Thus, it represents one of the most attracting targets for cancer therapy. Within the tumor mass, OPN is secreted in various forms either by the tumor itself or by stroma cells, and it can exert either pro- or antitumorigenic effects according to the cell type and tumor microenvironment. Thus, targeting OPN for therapeutic purposes needs to take into account the heterogeneous functions of the multiple OPN forms with regard to cancer formation and progression. In this review, we will describe the role of systemic, tumor-derived, and stroma-derived OPN, highlighting its pivotal role at the crossroads of inflammation and tumor progression.